2019
DOI: 10.1186/s12913-019-4688-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nurse staffing levels and nurse’s education on patient mortality in medical and surgical wards: an observational multicentre study

Abstract: BackgroundGrowing evidence indicates that improved nurse staffing in acute hospitals is associated with lower hospital mortality. Current research is limited to studies using hospital level data or without proper adjustment for confounders which makes the translation to practice difficult.MethodIn this observational study we analysed retrospectively the control group of a stepped wedge randomised controlled trial concerning 14 medical and 14 surgical wards in seven Belgian hospitals. All patients admitted to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 28 publications
2
51
0
4
Order By: Relevance
“…A shortage of nursing personnel severely affects the quality of medical services. This problem has been trending in most countries around the world (Buerhaus et al, 2007;Haddad and Toney-Butler, 2019;Haegdorens et al, 2019). Poland, however, has one of the lowest indicators of practicing nurses per 1000 residents among the OECD countries.…”
Section: Introductionmentioning
confidence: 99%
“…A shortage of nursing personnel severely affects the quality of medical services. This problem has been trending in most countries around the world (Buerhaus et al, 2007;Haddad and Toney-Butler, 2019;Haegdorens et al, 2019). Poland, however, has one of the lowest indicators of practicing nurses per 1000 residents among the OECD countries.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence over decades internationally showing that patients cared for in hospitals with more patients per nurse have worse outcomes including mortality, adverse events, infections and readmissions, compared with similar patients in hospitals with fewer patients per nurse. [1][2][3][4][5][6][7][8][9][10] Responding to this growing evidence, the International Council of Nurses released a position statement on safe staffing in 2018, encouraging nursing organisations and governments to establish evidence-based staffing systems and policies. 11 A policy intervention often discussed, but rarely implemented is setting minimum nurse-to-patient ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The major limitation of this study is related to the measurement of nurse staffing levels. International studies have measured nurse staffing levels in various ways, such nursing hours per patient day, nurse staffing by shift or the occupancy rate, and the education level of nurses [18,23,32]. However, this study only used the bed-to-nurse ratio because information on other indices was unavailable in the data used in this study; furthermore, this study could not control for the individual characteristics of nursing organizations and nurses due to limitations in the data.…”
Section: Hospital and Patient Characteristics And 30-day Postdischargmentioning
confidence: 99%
“…As such, in studies conducted in Korea, nurse staffing has consistently been found to be associated with multiple measures of mortality. Studies on nurse staffing and in-hospital deaths in other countries revealed associations between higher staffing levels of registered nurses and lower patient mortality rates [22,23]. Therefore, if an appropriate level of nurse staffing is secured, the mortality rate of patients could be expected to decrease.…”
Section: Bed-to-nurse Ratio and 30-day Post-discharge Mortalitymentioning
confidence: 99%